(3eaJGM GdadGM heUHGM GdCQhGM aj PcQ GdcQje GdaJGMs - (3CMeO Hf YWGA Gddg GdScfOQj, CHh GdYHGSs
(3ChdgG (B:s
(3GdMeO ddg aGJM CbaGd GdbdhH HPcQg hHYO aEf PcQ Gddg eaJGM GdadGM heUHGM GdCQhGM HaVd GdcQje GdaJGM s
(3BNQgG (B:s
(3hjdbGfi bHd GdCfHjGA hGdChdjGA CLeYjf hGdMeO ddg QH GdYGdejf ced cJGH eaJGM GdadGM s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(2 / 3773) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs